1984
DOI: 10.1037/0022-0663.76.6.1239
|View full text |Cite
|
Sign up to set email alerts
|

Informed Strategies for Learning: A program to improve children's reading awareness and comprehension.

Abstract: Children's awareness about their own cognitive skills, or metacognition, has been hypothesized to play a major role in their learning and development. This role was examined in an experimental study of third and fifth graders' reading comprehension. Children from four classrooms were given an experimental curriculum, Informed Strategies for Learning (ISL), that was designed to increase children's awareness and use of effective reading strategies. Children who participated in ISL made larger gains than did chil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
197
2
22

Year Published

1991
1991
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 436 publications
(234 citation statements)
references
References 26 publications
(23 reference statements)
8
197
2
22
Order By: Relevance
“…Or, expressed in another way, students have a good understanding of textual material, when they have successfully integrated information from the text with their prior knowledge, and thus are able to learn the new material (Kozminsky & Kozminsky, 2001). Paris, Cross and Lipson (1984) showed that some students in elementary education seemed to have difficulty in understanding the relationship between evidences and conclusions and this may make it difficult to see how words can provide clues to meaning within text. Long, Oppy and Seely (1994) argued that if readers are unable to generate inferences that connect explicit information in a text to relevant prior knowledge, they feel as though they do not comprehend the text and have difficulty remembering it.…”
Section: Text Comprehensionmentioning
confidence: 99%
“…Or, expressed in another way, students have a good understanding of textual material, when they have successfully integrated information from the text with their prior knowledge, and thus are able to learn the new material (Kozminsky & Kozminsky, 2001). Paris, Cross and Lipson (1984) showed that some students in elementary education seemed to have difficulty in understanding the relationship between evidences and conclusions and this may make it difficult to see how words can provide clues to meaning within text. Long, Oppy and Seely (1994) argued that if readers are unable to generate inferences that connect explicit information in a text to relevant prior knowledge, they feel as though they do not comprehend the text and have difficulty remembering it.…”
Section: Text Comprehensionmentioning
confidence: 99%
“…The literature underscores the need for comprehension instruction in these metacognitive strategies and emphasizes their central role in efficient reading (Alexander & Jetton, 2000;Almasi, 2003;Baumann & Schmitt,1986;Block & Pressley, 2002;Duffy et al, 1987;National Institute of Child Health and Human Development, 2000;Paris, Cross, & Lipson, 1984;Taylor & Duke, 2013). Responsive, engaged, and thoughtful readers who critically evaluate texts will go beyond pronouncing words correctly and quickly because they are actively involved in constructing meaning and responding appropriately.…”
Section: Assessment Of Metacognitive Strategy Knowledgementioning
confidence: 99%
“…Instruction in this important component has proven to be an important aspect of classroom curricula (Alexander & Jetton, 2000;Almasi, 2003;Baumann, Jones, & Seifert-Kessell, 1993;Fielding & Pearson, 1994;Paris, Cross, & Lipson, 1984;Paris & Jacobs, 1984;Pressley, 2000;Schmitt, 1990). However, this was not always the case.…”
mentioning
confidence: 99%
“…Sometimes it is necessary to teach the right learning strategy at just the time it is needed, and to point out why it is an appropriate strategy to use. Younger or low ability learners, for example, require complete, explicit instruction that is situated in the context of the domain being studied (Campione, 1987;Loper & Murphy, 1985;Paris, Cross, & Lipson, 1984;Pressley, 1986).…”
Section: Effectiveness Of Learning Strategy Trainingmentioning
confidence: 99%